I design of a wireless System Wavepoint Low Plataform Linux - Muñoz Vara, Eddie Raúl (2005)
This paper develops the implementation of a system that uses the spectrum spread through wireless cards of the company Lucent Technologies (to 10 Mb/s). The main objective was to establish a connection wireless among PC's with connection to Internet. The wireless servant (wavepoint) it was implemented in platform Linux, for that which necessary fuel to design a driver that allows tocontrol a Card Wave LAN. The users they have the capacity to work in system operative Windows or Linux. The controllers for wireless cards in platform Linux, but they have speeds of 2 MB/s the one, which with the designed driver you arrives to speeds of 10 MB/s. This system implemented in one personal computer with minimum requirements of hardware, it is known commercially as access point it produces it the company Lucent Technologies and its name commercial it is "Wave Point"whose cost you the 2,000 USD approaches. The cost of the one developed device has and I price of around the 800 dollars, with the same functionality. One of the important tests was to determine the maximum distances of operation of the system, to check that this it is system it is good to comparison of a technology of more cost.